A Fixed Point Approach to the Stability of a General Mixed AQCQ-Functional Equation in Non-Archimedean Normed Spaces - Tian Zhou Xu; John Michael Rassias; Wan Xin Xu (Discrete Dynamics in Nature and Society)
Using the fixed point methods, we prove the generalized Hyers-Ulam stability of the general mixed additive-quadratic-cubic-quartic functional equation f(x+ky)+f(x−ky)=k2f(x+y)+k2f(x−y)+2(1−k2)f(x)+((k4−k2)/12)[f(2y)+f(−2y)−4f(y)−4f(−y)] for a fixed integer k with k≠0,±1 in non-Archimedean normed spaces.